The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1590/s1982-56762009000100002
|View full text |Cite
|
Sign up to set email alerts
|

Plant growth promoting rhizobacteria as agents in the biocontrol of eucalyptus mini-cutting rot

Abstract: The effectiveness of ten plant growth-promoting rhizobacteria (PGPR) was evaluated for the control of mini-cutting rot of eucalyptus caused by Cylindrocladium candelabrum and Rhizoctonia solani. Inhibition of the "in vitro" mycelial growth of each pathogen differed with PGPR isolate and culture medium evaluated. The most effective group of isolates was FL2 (Pseudomonas sp.), 3918, S1 and S2 (Bacillus subtilis). Under nursery conditions, isolate Ca (Pseudomonas fulva) reduced the incidence of mini-cutting rot c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 30 publications
0
14
0
2
Order By: Relevance
“…Thus far however, the majority of the reports from Brazil focused on forestry crops, such as Pinus and Acacia ( Hodges and May, 1972 , Hodges et al., 1973 , Alfenas, 1986 , Dianese et al., 1986 , Novaes et al., 2012 , Alfenas et al., 2013a , Alfenas et al., 2013b ) and in particular on the epidemiology and disease control of Calonectria spp. associated with diseases of Eucalyptus in commercial plantations and nurseries ( Blum et al., 1992 , Mafia et al., 2008 , Mafia et al., 2009 , Graça et al., 2009 , Ferreira et al., 2012 , Alfenas et al., 2013c ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus far however, the majority of the reports from Brazil focused on forestry crops, such as Pinus and Acacia ( Hodges and May, 1972 , Hodges et al., 1973 , Alfenas, 1986 , Dianese et al., 1986 , Novaes et al., 2012 , Alfenas et al., 2013a , Alfenas et al., 2013b ) and in particular on the epidemiology and disease control of Calonectria spp. associated with diseases of Eucalyptus in commercial plantations and nurseries ( Blum et al., 1992 , Mafia et al., 2008 , Mafia et al., 2009 , Graça et al., 2009 , Ferreira et al., 2012 , Alfenas et al., 2013c ).…”
Section: Introductionmentioning
confidence: 99%
“…Antifungal activity of selected isolates was assessed against F. oxysporum, root rot causing pathogen of V. radiata L. (Anderson 1985). Mafia et al (2009) isolated bacteria that showed strong antagonism against F. oxysporum and identified as belonging to the genus Bacillus. In our study six isolated culture showed antagonist activity against F. oxysporum.…”
Section: Discussionmentioning
confidence: 99%
“…The genera Bacillus and Pseudomonas are the most common microorganisms used as biocontrol agents [23][24][25][26]. Otherwise, few studies tested the effect of secondary metabolites produced by bacteria in the control of contaminants microorganisms during the fuel ethanol production [27].…”
Section: Discussionmentioning
confidence: 99%